The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1002/bbb.2192
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between US and Brazilian ethanol prices: new evidence based on fractal regressions

Abstract: Two different fractal regression methodologies were employed with the aim of understanding the relationship between prices of ethanol produced in the USA and Brazil, the most important producers of ethanol. These methodologies, which have the advantage of giving us information about the relationships between different timescales, could also provide interesting and important information about this particular market. Our results suggest, first, some differences in the basic price in these markets, and second, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…Despite the positive correlation between Brazilian ethanol and international oil prices, a large part of the Brazilian ethanol supply is absorbed by domestic market demand, which tends to limit the transmission of international price shocks to domestic prices in the short term. The lower correlation between CBIOS prices and ethanol prices is in line with the results of Quintino et al ( 2021a ), who studied the EU Allowance (EUA) emission prices and Brazilian ethanol prices and showed that the relationship is weak and short term.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Despite the positive correlation between Brazilian ethanol and international oil prices, a large part of the Brazilian ethanol supply is absorbed by domestic market demand, which tends to limit the transmission of international price shocks to domestic prices in the short term. The lower correlation between CBIOS prices and ethanol prices is in line with the results of Quintino et al ( 2021a ), who studied the EU Allowance (EUA) emission prices and Brazilian ethanol prices and showed that the relationship is weak and short term.…”
Section: Resultssupporting
confidence: 88%
“…Several studies, including those by David et al ( 2020 ), Hallack et al ( 2020 ), Nascimento Filho et al ( 2021 ), Quintino et al ( 2022 ), and Palazzi et al ( 2022 ), have investigated the impact of this policy on fuel prices. Additionally, Dutta and Bouri ( 2019 ) and Quintino et al ( 2021a ) have contributed to the understanding of price relationships of carbon emission prices in the context of the Brazilian sugarcane and ethanol sector.…”
Section: Introductionmentioning
confidence: 99%
“…Another recently explored topic is the possible relationship between Brazilian ethanol spot and futures prices at the Brazilian Exchange, B3 [14,15], as well as the possible relationship between ethanol prices in the Brazilian and USA markets [15][16][17][18][19].…”
Section: Literature Reviewmentioning
confidence: 99%
“…determined whether the detection of structural breaks improves the forecast of future prices, and Dutta, 24 Hernandez et al 25 . and Quintino et al 26 . studied the relationship between Brazilian and US ethanol.…”
Section: Introductionmentioning
confidence: 99%
“…Notable recent contributions include Dutta 22,24 and Bouri et al 23 Considering the US market, bearing in mind that corn is used for the production of US ethanol, Dutta 22 studied whether the implied volatility of corn helps in predicting future corn price returns. With regard to US ethanol, Bouri et al 23 determined whether the detection of structural breaks improves the forecast of future prices, and Dutta, 24 Hernandez et al 25 and Quintino et al 26 studied the relationship between Brazilian and US ethanol. Concerning the price of sugar, Amrouk and Heckelei 27 used a Bayesian model to make forecasts of international sugar prices.…”
mentioning
confidence: 99%